Maternal cardiovascular risk in early and late onset of preeclampsia patients five years after labor : A comparative study - Ernawati, - (DR.P.R.YADAV, 2019)
ABSTRACT : Preeclampsia still remains an important topic in relation to the cardiovascular system in more than 300 million women worldwide, with both short and longterm mobidities. The purpose of this study was to compare maternal cardiovascular risk of early and lateonsets of preeclampsia 5 years after labor. It was a retrospective cohort study of preeclampsia patients within the period of January 2013 to January 2014, who delivered at Dr. Soetomo General Hospital. The maternal cardiovascular risk assessment include; body mass index (kg/m2), waist circumference (cm), blood pressure (mmHg), fasting blood sugar levels (mg/dL), HDL cholesterol levels (mg/dL), LDL cholesterol levels (mg/dL), blood triglyceride levels (mg/dL), total cholesterol levels (mg/dL) and ATP-III Framingham scores. There was a higher and significant cardiovascular risk factors in relations to hypertension and/or metabolic syndrome (p 0.031) in the early-onset of severe preeclampsia group, which also supported an increase of 1.47 folds of cardiovascular risks (RR 1..471; CI 95 [1.071-2.019]) compared with the late-onset group. The incidence of metabolic syndrome 5 years after preeclampsia was higher in the early-onset of preeclampsia group compared with the late-onset. Also, the cardiovascular risk factors related to hypertension and / or metabolic syndrome were higher in the early-onset group and supported an increase in cardiovascular risk factors of 1.47 times compared with the late-onset group.